Millennial Political Concerns and Political Preferences towards Presidential Election in 2019: Evidence from Palembang - Ainur Ropik; Mariatul Qibtiyah (Jurnal Studi Sosial dan Politik, 2021)
The 2019 democratic party was dominated by millennial generation voters. In the face of the democratic party for the presidential/vice presidential election which was held in 2019, the millennial generation is a group of potential voters whose the largest voting rights because it influences in determining who the candidate for the nation's leader is. This study uses a mixed method research, which combines qualitative and quantitative research methods with analytical descriptive to obtain more in-depth data. This study seeks to reveal the political preferences of the millennial generation of Palembang in the presidential election 2019. By using the theory of voting behavior, this study attempts to analyze the political preference factors of the millennial generation in the presidential election 2019. The results of this study indicate that the political preferences of the millennial generation of Palembang in the presidential election 2019 based on several factors, namely sociological factors, psychological factors, and the rational choice of the millennial generation in determining the candidates they choose. The political rights of the millennial generation is important because of the position of the millennial generation as a generation that has the potential to determine the life of a better Indonesian political system.